Correction: A line-broadening free real-time 31P pure shift NMR method for phosphometabolomic analysis. Issue 22 (20th October 2021) - Kaup, Karl Kristjan; Toom, Lauri; Truu, Laura; Miller, Sten; Puurand, Marju; Tepp, Kersti; Käämbre, Tuuli; Reile, Indrek
Abstract : Correction for 'A line-broadening free real-time 31 P pure shift NMR method for phosphometabolomic analysis' by Karl Kristjan Kaup et al., Analyst, 2021, 146, 5502–5507, DOI: ; 10.1039/D1AN01198G .